ATRANORIN SECONDARY METABOLITE FROM LICHEN Usnea sp. AND ITS ANTIBACTERIAL ACTIVITY - MAULIDIYAH; SITTI HADIJAH SABARWATI; EKA SAFUTRA; MUHAMMAD NURDIN (International Journal of Pharma and Bio Sciences, 2016)
Isolation and identification of secondary metabolites from lichen Usnea sp. fraction of n-hexane and its activity against bacteria have been carried out. The isolation was done by maceration extraction with methanol, then performed a partition with n-hexane solvent. Fractions of n-hexane was then separated by gravity column chromatography (GCC) and thin layer chromatography (TLC) techniques using a gradient eluent mixture of nhexane : ethyl acetate. The results of data analysis-1D NMR spectroscopy (1H and 13C-NMR), 2D NMR (HMQC, HMBC and 1H-1H COSY) were compared with similar data from the literature. The isolated compound was identified as atranorin. The antibacterial activities test were applied on the fraction of n-hexane and isolated compound. Test results of n-hexane fraction activity against Escherichia coli (ATCC 35218), Staphylococcus aureus (ATCC 25923) and Salmonella typhi (YCTC) with a diameter of inhibition zone on the concentration of 500 mg/mL were 9.33, 10.6 and 10.6 mm, respectively. While, test of isolated compound activity against the same three types of bacteria at concentrations of 500 mg/mL were 3.0, 4.0 and 5.3 mm, respectively.